2006 American Control Conference 2006
DOI: 10.1109/acc.2006.1657380
|View full text |Cite
|
Sign up to set email alerts
|

An auction algorithm for allocating fuel in satellite constellations using peer-to-peer refueling

Abstract: The problem of assuring the operability of a satellite constellation by internal (peer-to-peer/P2P) refueling is addressed. Specifically, a formulation is presented that seeks to match the fuel-sufficient satellites in the constellation with the fuel-deficient ones, so that the former can refuel the latter, while at the same time minimize the total fuel consumption incurred during the ensuing orbital rendezvous. Asymmetric auctions are introduced as a means for solving this problem, owing to their advantages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…[17], same as in Ref [22][23][24][25][26]. While some others solved the problem by converti ng it into an Optimal Matching Problem (OMP) [18][19] or a mixed mode [20][21].…”
Section: Mtmmentioning
confidence: 99%
See 1 more Smart Citation
“…[17], same as in Ref [22][23][24][25][26]. While some others solved the problem by converti ng it into an Optimal Matching Problem (OMP) [18][19] or a mixed mode [20][21].…”
Section: Mtmmentioning
confidence: 99%
“…The PTP refueling model, which established by Ref. [28], added fuel quantity t hreshold as a new parameter, where targets with larger quan tity as fuel-abundant and smaller quantity as fuel-deficient. Furthermore, some scholars assumed that each service satell ite can return to the original position of anyone after rendez vous, transformed it into a three-index assignment problem, also called E-PTP (Egalitarian Peer to Peer) problem, and s olved it by using search algorithms [29].…”
Section: Ptpmentioning
confidence: 99%
“…In these kind of strategies, each satellite can play the role of the refueling/ servicing spacecraft (Shen and Tsiotras, 2005;Dutta and Tsiotras, 2009). Systematical studies have been performed on P2P and mixed refueling strategies (Dutta and Tsiotras, 2006), and it has been shown that a mixed refueling strategy consumes less fuel than a strategy with only one service satellite for a large number of satellites and for short refueling periods (Tsiotras and de Nailly, 2005 (Salazar and Tsiotras, 2006;Dutta andTsiotras, 2006, 2008;Dutta, 2009). P2P refueling strategy using low-thrust propulsion has also been investigated (Dutta et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, although not focused on debris mitigation, Ceriotti and Vasile incorporated an ant colony optimization algorithm within a scheme to generate interplanetary gravity-assist trajectories (Ceriotti and Vasile, 2010). On the other hand, market-based auction algorithms have been successfully applied to spacecraft constellation design and operations (de Weck et al, 2008;Salazar and Tsiotras, 2006;Hilland et al, 2001), though they have yet to be applied to the mitigation of space debris or similar spacecraft routing problems.…”
Section: Introductionmentioning
confidence: 98%